Use of Google Meet Media in Online Learning for Islamic Religious Education at SMA Negeri 5 Kupang City-NTT for the 2020/2021 Academic Year - Samsudin Amir; Bambang Sumardjoko; Hafidz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Online learning is a learning method that is carried out by not carrying out teaching and learning activities directly face to face but by utilizing internet-based information media using communication tools such as cellphones and laptops using the Google Meet application remotely. Google Meet is a videoconference application that can connect many people in one online space and can communicate and see each other virtually. Learning using Google Meet can affect students' liveliness levels during online learning. Learning effectiveness is an activity carried out by a teacher who motivates students by using special approaches and strategies to achieve a learning goal well. A lesson can be said to be effective if it is carried out well and achieved in accordance with the expected goals.